GANGGUAN PSIKOGENIK LATAH GARY ISKAK: KAJIAN PSIKOLINGUISTIK - Nuril Phasa, Hidayah (Universitas Ahmad Dahlan, 2022)
This research is motivated by the stigma of talkativeness suffered by women, people with low education, and belonging to the lower economic class category. The research entitled